Fabrication of metallic parts with overhanging structures using the robotic wire arc additive manufacturing. (March 2021) - Yuan, Lei; Pan, Zengxi; Ding, Donghong; Yu, Ziping; van Duin, Stephen; Li, Huijun; Li, Weihua; Norrish, John
Highlights: A theoretical analysis of the metal transfer behaviour and bead shape formation using positional GMAW are provided. The effects of various process parameters on the stability of positional deposition are investigated. The effectiveness of the proposed strategy is verified by three complex samples using a positional GMAW-WAAM process. Abstract: Robotic wire arc additive manufacturing (WAAM) technology has been widely employed to fabricate medium to large scale metallic components. It has the advantages of high deposition rates and low cost. Ideally, the deposition process is carried out in a flat position. The build direction is vertically upward and perpendicular to a horizontal worktable. However, it would be difficult to directly deposit complex parts with near horizontal 'overhangs', and temporary supports may be required. Thus, it is necessary to find an alternative approach for the deposition of 'overhangs' without extra support in order to simplify the deposition set-up. This paper proposed a fabrication method of producing metallic parts with overhanging structures using the multi-directional wire arc additive manufacturing. Firstly, based on the metal droplet kinetics and weld bead geometry, two different Gas Metal Arc Welding (GMAW) metal transfer modes, namely short circuit transfer and free flight transfer, were evaluated for the multi-directional wire arc additive manufacturing. Subsequently, the effects of process parameters, including wire feed speed (WFS), torch travel speed (TS), nozzle to work distance (NTWD) and torch angle, on the stability of positional deposition were investigated. Finally, the effectiveness of the proposed strategy was verified by fabricating three complex samples with overhangs.